Tobacco Advertising Features That May Contribute to Product Appeal Among US Adolescents and Young Adults. Issue 8 (29th December 2020) - Moran, Meghan Bridgid; Heley, Kathryn; Czaplicki, Lauren; Weiger, Caitlin; Strong, David; Pierce, John
Abstract: Introduction: Cigarette advertising is a causal agent of smoking uptake among young people. Although prior research links ad receptivity to tobacco product interest and use, little is known regarding the specific advertising tactics associated with increased product appeal among young people. Methods: A national sample of 13–20 year-olds ( N = 3688, youth) and 21–24 year-olds ( N = 1556, young adults) in the US participated in an online survey in 2017 (mean age 18.1 years). The majority (72.0%) of youth and nearly half (44.8%) of young adults were never smokers. Participants were shown a cigarette ad, randomly assigned from a pool of 50 advertisements, and reported how much they liked the ad, and were curious about and interested in using the advertised product. All 50 advertisements were content analyzed for a variety of features. Data from the survey and content analysis were merged and mixed effects analyses used to identify the features associated with increased liking, curiosity, and interest in using, referred to collectively as product appeal. Results: Presence of a sweepstakes offer was associated with increased liking, curiosity and interest among youth and curiosity and interest among young adults. Outdoors settings, flora imagery, natural descriptors, and environmental themes were associated with increased appeal. Price reductions (eg, coupons) were associated with decreased appeal among youth. Conclusions: This study identified several advertising tactics associated with increased appeal among youth and young adults. If additional research confirms these findings, the U.S. Food and Drug Association should consider restricting use of these tactics in tobacco advertising. Implications: This study's findings provide insight into features of cigarette ads that appeal to youth and young adults. Overall, the presence of sweepstakes appealed to youth and young adults and outdoors and environmental themes were particularly appealing to young adults. Such tactics could serve to further brand engagement, improve brand image and lead to initiation or escalation of use. If confirmatory studies further demonstrate the effects of the tactics identified in this study on youth product appeal, U.S. Food and Drug Administration should consider using its authority to restrict the use of youth-appealing tactics.